From permeability modelling to particle deposition in human lung : an overview of activities at the Division of Fluid Mechanics, Luleå University of Technology - Lundström, Staffan (Luleå tekniska universitet, Strömningslära och experimentell mekanik, 2007)
Modelling of flow through porous media has been a main research track at the Division of Fluid Mechanics at Luleå University of Technology all since the derivation of Gebart's permeability model in 1992. This model for parallel cylinders has gained great attention and has been extended to flow through perturbed arrays as well as arrays with an arbitrary orientation. Even more, an apparent permeability of an idealized unidirectional reinforcement has been derived for power-law fluid flow perpendicular to the cylinders and the modelling is currently developed for high Reynolds number flow in connection to inner erosion in embankment dams. By usage of Computational Fluid Dynamics (CFD) also more complex structures have been modelled. An example of this is non-crimp fabrics that consists of fibres stitched together in bundles.The two-scale porosity that results is interesting as such but becomes even more fascinating if the impregnating fluid contains particles. It may then happen that the particles are filtrated at the boundaries of the fibre bundles, as visualised by m-PIV, and hence an in-homogenous distribution is obtained. CFD modelling is also introduced for drying of iron ore pellets. In this case heated air is allowed to flow through a bed of green pellets with high water content and the trick is to carry out this procedure without breaking the rather fragile pellets. The flow between the pellets is assumed to be turbulent and it is interesting to know to what extent variations in local flow velocity result in inhomogeneous drying and finally a variation in the properties of the dried and sintered pellets. Work has furthermore been done when dense fibre suspensions are forced to move in pressing of Sheet Moulding Compound. Experimental visualisations yield a complex flow and instead of taking a micromechanical approach inverse modelling is applied with increasing complexity of the rheological model. Recently, a study on the effects upon inhalation of micro- and nano-particles has been launched. A multiply ...